دور الآراء المخالفة والمنفردة لقضاة محكمة العدل الدولية في تطوير القانون الدولي - لعبيدي, الأزهر; الأخضري, نصر الدين (جامعة الوادي University of Eloued, 2018)
ملخص: يتناول موضوع هذه الدراسة أحد أهم آليات الخلاف المؤسسي على مستوى الهيئة القضائية الرئيسية للأمم المتحدة، وذلك من خلال فكرتي الآراء المنفردة والمخالفة التي يلحقها قضاة محكمة العدل الدولية بقرارات هته الأخيرة وفقا لنص المادة 57 من النظام الأساسي للمحكمة وكذا نصي الفقرتين 02 و03 من المادتين 95 و107 من لائحة المحكمة (1978) على التوالي. وعلى هذا الأساس سنحاول ضمن طيات هذه الدراسة تقييم العملية القضائية الدولية بوصفها عاملا في تطوير قواعد القانون الدولي أو العكس. Abstract: The present study deals with one of the most important mechanisms of institutional dispute at the level of the principal judicial body of the United Nations through the dissenting and separate opinions of the judges of the International Court of Justice in accordance with the provisions of article 57 of the Statute of the Court, as well as the texts of paragraphs 02 and 03 of articles 95 and 107 which are taken from the Rules of the Court (1978), respectively. We will basically attempt to evaluate the international judicial process as a factor in the development of the rules of the international law or vice versa.
Keywords: الآراء؛ المخالفة؛ المنفردة - قضاة؛ محكمة؛ العدل؛ القانون؛ الدولي; dissenting; separate; opinions; judges; International; Court; Justice; development; law